Nanorods Based on Mesoporous Silica Containing Iron Oxide Nanoparticles as Catalytic Nanomotors: Study of Motion Dynamics. Issue 2 (1st December 2020) - Mestre, Rafael; Cadefau, Núria; Hortelão, Ana C.; Grzelak, Jan; Gich, Martí; Roig, Anna; Sánchez, Samuel
Abstract: Self‐propelled particles and, in particular, those based on mesoporous silica, have raised considerable interest due to their potential applications in the environmental and biomedical fields thanks to their biocompatibility, tunable surface chemistry and large porosity. Although spherical particles have been widely used to fabricate nano‐ and micromotors, not much attention has been paid to other geometries, such as nanorods. Here, we report the fabrication of self‐propelled mesoporous silica nanorods (MSNRs) that move by the catalytic decomposition of hydrogen peroxide by a sputtered Pt layer, Fe2 O3 nanoparticles grown within the mesopores, or the synergistic combination of both. We show that motion can occur in two distinct sub‐populations characterized by two different motion dynamics, namely enhanced diffusion or directional propulsion, especially when both catalysts are used. These results open up the possibility of using MSNRs as chassis for the fabrication of self‐propelled particles for the environmental or biomedical fields. Abstract : Mesoporous silica nanorods (MSNRs) are presented as interesting new chassis for the development of catalytic nanomotors due to their longitudinal pores, their rod‐like structure and versatile material. Three types of MSNR nanomotors, based on Pt catalysis, Fenton‐like reactions of embedded Fe2 O3 nanoparticles inside the mesopores, and their synergistic combination, are demonstrated to self‐propel upon addition of hydrogen peroxide. Two sub‐populations of motors moving by either enhanced diffusion or ballistic propulsion are shown to coexist in this system.